Design and Numerical-Method-Aided Optimization of a Novel Attachment System for Implant-Retained Dental Prostheses Using NiTi Shape Memory Alloys - Shayanfard, Pejman; Wendler, Frank; Hempel, Philipp; Karl, Matthias (Applied Sciences, 2023)
While nickel-titanium (NiTi) is the primary shape memory alloy (SMA) used in endodontic instruments, restorative dental components so far have not been fabricated from SMAs. The flexibility of these materials may solve problems in implant prosthodontics resulting from non-parallel implant positions and transfer inaccuracies. Based on a prototype of a novel attachment system for implant overdentures, a finite element model was created and used for studying different loading situations and design parameters followed by numerical analysis aided design optimization. The results revealed that the basic design of the attachment is capable of compensating misalignments of supporting implants as well as transfer inaccuracies of a clinically relevant magnitude by accommodating the large deformations induced under masticatory loading upon martensitic phase transformation at almost constant stress. The application of NiTi resulted in the reduction of the reaction forces recorded in the surrounding of the supporting implant, as well, the reaction forces between male and female parts of the attachment system could be reduced which will minimize wear phenomena and subsequent maintenance costs. These effects were seen to be enhanced in the optimized design.
CRIS-Team WoS Importer:2023-01-27